(S)-5-Benzyl- and 5-benzylidene-imidazo-4-onederivatives synthesized and studied for anunderstanding of their thermal reactivity - Pepino, Ana Julieta (2014)
Flash vacuum as well as static pyrolysis were used to gain insight into the mechanisms of decomposition ofthe title compounds. They were synthesized by the use of microwave techniques that allowed better yieldsthan the established methods. Since the benzyl compounds always open a radical channel in the thermalprocesses, consequently lowering the yields of other important intramolecular processes, we also startedthe pyrolysis with benzylidene derivatives. Detection and quantification of products accompanied bykinetic analyses were carried out for both types of compounds. The activation energies as well as theentropy contributions have been determined. Moreover, DFT calculations provided support for andcorroborating of the proposed thermal pathways.